THE UNIVERSITY OF BELGRADE ON ARWU LIST: Part I: THE IMPACT OF INDIVIDUAL FACULTIES ON THE ACHIEVED POSITION USING PROMETHEE-GAIA METHOD - Zivkovic, Zivan; Arsić, Milica; Nikolic, Djordje (Serbian Journal of Management, 2017)
Since 2012, University of Belgrade (UB) has been ranked among the 500 best universities in the world on the prestigious Academic Ranking of World Universities (ARWU) list, also known as Shanghai list. These top 500 universities represent only 2% of all universities in the world. According to the most recent global ranking done in 2015, UB ranks between 201 and 300 place, and is the best ranked university in Southeast Europe. UB consists of 31 faculties and 11 research institutes and each of these institutions in its own way contributes to the overall achieved position of UB on the ARWU list. This paper analyzes the impact of its certain faculties on the UB’s ranking position through a number of papers indexed in Science Citation Index - SCIe and SSCI, the number of citations and the number of citations per paper and per researcher for the period 2011 - 2015. For data processing multi-criteria decision making method PROMETHEE-GAIA, was used. Obtained results revealed four clusters of faculties such as faculties – with the greatest impact, with a significant impact, medium and low impact on the overall ranking result on ARWU list.